(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the effect of project-based learning (PjBL) integrated with arts on the socio-emotional development and creativity of early childhood. The research employed a quasi-experimental design with a one-group pretest-posttest approach, involving 28 Group B children at TK Angkasa, Magetan Regency. The intervention was implemented in five PjBL stages: project introduction, collaborative planning, implementation of art activities (drawing, collage, and loose parts installation), project presentation, and reflection. The observation sheet was used as the main instrument, and data were analyzed using the Paired Sample t-Test with SPSS version 26. The results showed a significant increase in socio-emotional scores (from 11.86 to 15.43) and creativity (from 12.14 to 16.07), with a significance value of p < 0.05. Qualitative findings also indicated that children actively participated, collaborated effectively, and expressed themselves creatively. These findings suggest that art-based PjBL is effective in developing young children’s social skills and creativity.